SOME BIOLOGICAL OBSERVATIONS ON THE WHITE WHALE FROM THE AIRCRAFT(Nekotorye Biologicheskie Nablyudenity za Belukhoi s Samoleta) - Belkovich,V. M. (1968)
On the basis of observations on the white whale carried out from the airplane in June and July 1957 in the White, Barents and Kara Seas, it was found that in summer herds of up to 10 animals are prevailing (54.9% of occurrence). Single animals and aggregations of several hundreds are seldom observed (16.1 and 3.2% of occurrence, respectively) and represent a temporary phenomenon. The main constant group of the herd is a female with one-three young of different age; during the breeding season these groups are joined by males, and a mixed herd consists of groups of two-five animals in each. Herds of adult white whales without the young seem to consist of males only which form groups of 3-15 animals. The time of bearing young somewhat shifts in white whales with their advance eastward; in the White Sea they bear young in the mid or the end of June, in Barents Sea in early July, in the Kara Sea in mid-July. (Author) Trans. of Zoologicheskii Zhurnal (USSR) v39 n9 p1414-1422 1960, by M. Slessers.